Novel injectable, self-gelling hydrogel–microparticle composites for bone regeneration consisting of gellan gum and calcium and magnesium carbonate microparticles. (21st November 2016) - Douglas, Timothy E L; Łapa, Agata; Reczyńska, Katarzyna; Krok-Borkowicz, Małgorzata; Pietryga, Krzysztof; Samal, Sangram Keshari; Declercq, Heidi A; Schaubroeck, David; Boone, Marijn; Van der Voort, Pascal; De Schamphelaere, Karel; Stevens, Christian V; et al.
Abstract: The suitability of hydrogel biomaterials for bone regeneration can be improved by incorporation of an inorganic phase in particle form, thus maintaining hydrogel injectability. In this study, carbonate microparticles containing different amounts of calcium (Ca) and magnesium (Mg) were added to solutions of the anionic polysaccharide gellan gum (GG) to crosslink GG by release of Ca 2+ and Mg 2+ from microparticles and thereby induce formation of hydrogel–microparticle composites. It was hypothesized that increasing Mg content of microparticles would promote GG hydrogel formation. The effect of Mg incorporation on cytocompatibility and cell growth was also studied. Microparticles were formed by mixing Ca 2+ and Mg 2+ and CO 3 2 − ions in varying concentrations. Microparticles were characterized physiochemically and subsequently mixed with GG solution to form hydrogel–microparticle composites. The elemental Ca:Mg ratio in the mineral formed was similar to the Ca:Mg ratio of the ions added. In the absence of Mg, vaterite was formed. At low Mg content, magnesian calcite was formed. Increasing the Mg content further caused formation of amorphous mineral. Microparticles of vaterite and magnesium calcite did not induce GG hydrogel formation, but addition of Mg-richer amorphous microparticles induced gelation within 20 min. Microparticles were dispersed homogeneously in hydrogels. MG-63 osteoblast-like cells were cultured in eluate from hydrogel–microparticle composites and on the composites themselves. All composites were cytocompatible. Cell growth was highest on composites containing particles with an equimolar Ca:Mg ratio. In summary, carbonate microparticles containing a sufficient amount of Mg induced GG hydrogel formation, resulting in injectable, cytocompatible hydrogel–microparticle composites.